Supply chain flexibility concepts, dimensions and outcomes: an organisational capability perspective. Issue 17 (2nd September 2018) - Huo, Baofeng; Gu, Minhao; Wang, Zhiqiang
Abstract : Due to the increasing uncertainty and diversity in supply chains (SCs), companies are aiming to develop their SC flexibility, which we define as the capability of a company, both internally and externally in conjunction with its key suppliers and customers, to respond to uncertainties and customer expectations without excessive costs, time and performance losses. SC flexibility has three dimensions – internal, supplier and customer flexibility. This study investigates how SC flexibility improves operational and financial performance from the organisational capability perspective. The conceptual model is empirically tested using data collected from 216 companies in China. Our findings suggest that only customer and internal flexibility contribute to operational performance directly, while supplier flexibility contributes to operational performance only indirectly through internal flexibility. The three dimensions of SC flexibility have no direct impacts on financial performance. We further identify complementarities between supplier and customer flexibility and tradeoffs between supplier and internal flexibility. However, no synergy effect is found for internal and customer flexibility on operational performance. This study provides a framework to understand SC flexibility from the organisational capability perspective and identifies the inter-relationships among the three dimensions of SC flexibility and operational and financial performance.